??-Deferred Statistical Convergence of Fractional Order - Aral, Nazlim Deniz; Kandemir, Hacer Sengul; Et, Mikail (Amer Inst Physics, 2021)
In this paper, we introduce the concepts of Delta(alpha)-deferred statistical convergence with the fractional order of alpha and Delta(alpha) strongly convergence with the fractional order of alpha. Additionally, we give some relations about these concepts.
4th International Conference of Mathematical Sciences (ICMS) -- JUN 17-21, 2020 -- Maltepe Univ, ELECTR NETWORK
Keywords: Statistical convergence; deferred statistical convergence; difference sequence